2017
DOI: 10.3390/antibiotics6030017
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Staphylococcus aureus Cellular Pathways Affected by the Stilbenoid Lead Drug SK-03-92 Using a Microarray

Abstract: The mechanism of action for a new lead stilbene compound coded SK-03-92 with bactericidal activity against methicillin-resistant Staphylococcus aureus (MRSA) is unknown. To gain insight into the killing process, transcriptional profiling was performed on SK-03-92 treated vs. untreated S. aureus. Fourteen genes were upregulated and 38 genes downregulated by SK-03-92 treatment. Genes involved in sortase A production, protein metabolism, and transcriptional regulation were upregulated, whereas genes encoding tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 93 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…Based on prior work, we hypothesized that the SK-03-92 treatment affected a putative regulatory system labeled BrpR/S, which led to the release of a lethal factor such as an autolysin, mutacin, holin, or bacteriocin that rapidly killed the S. aureus cells. A previous microarray study of SK-03-92 treated versus untreated S. aureus cells demonstrated that three genes could be tied to a potential mechanism of action of the SK-03-92 drug: brpR, brpS, and lrgA [10]. The brpR and brpS genes had the highest differences in transcript abundance when comparing treated versus untreated cells.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Based on prior work, we hypothesized that the SK-03-92 treatment affected a putative regulatory system labeled BrpR/S, which led to the release of a lethal factor such as an autolysin, mutacin, holin, or bacteriocin that rapidly killed the S. aureus cells. A previous microarray study of SK-03-92 treated versus untreated S. aureus cells demonstrated that three genes could be tied to a potential mechanism of action of the SK-03-92 drug: brpR, brpS, and lrgA [10]. The brpR and brpS genes had the highest differences in transcript abundance when comparing treated versus untreated cells.…”
Section: Discussionmentioning
confidence: 98%
“…Transcript abundance differences were the greatest for the MW2284 and MW2285 genes (14.1-and 26.3-fold less, respectively) following treatment with SK-03-92 compared to the untreated cells [10]. Transcription of the lrgA gene also fell 3.2-fold in the drug treated cells versus untreated cells.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…All of the RT-qPCRs were performed using the iTaq Universal SYBR Supermix kit according to manufacturer’s instructions (BioRad, Hercules, CA, USA). Primers used in this study have been used in other studies: ftsZ [58], ssl5 [33], and ssl8 [33] and were synthesized by Integrated DNA Technologies (Coralville, IA, USA). A CFX96 machine (BioRad, Hercules, CA, USA) was used throughout the study.…”
Section: Methodsmentioning
confidence: 99%